Crisis communication management government public relation of Serang City through digital media - Sjuchro, Dian Wardiana; Priana, Ronny Yudhi Septa; Fitriana, Rina; Raji, Mohd Nazri Abdul (PRofesi Humas, 2026)
Background: The development of digital media accelerates the flow of public information and sometimes facilitates disinformation that affects the public’s image and trust in local governments. It requires their public relations (PR) to be able to manage information, messages, and media to enhance positive images within the community. Purpose: This study aimed to analyze the role of PR in Serang City in managing communication crises in the digital media era; then to reveal the effectiveness of PR communication strategies and uncover the obstacles encountered. Methods: This research employed a qualitative approach with a case study method. Data were obtained through in-depth interviews with PR staff and media officers from eight regional government agencies (OPD). Data were analyzed through reduction, presentation, and conclusion. Results: The PR of Serang City monitored current issues developing in the community, compiled and designed official messages, and utilized social media as the primary communication channel. This strategy was deemed effective in maintaining the stability of public information. Limited human resources and the rapid spread of hoaxes in the digital space were challenges faced, in addition to the lack of coordination and consistency of information within the government. Conclusion: crisis communication management is implemented by local governments using digital media as the main communication medium, but human resource competencies remain limited to improving coordination and designing more systematic communication so that information can be more effective and consistent. Implications: The results of this study are expected to be a reference for local governments to improve human capacity and build an integrated communication system to maintain credibility and public trust.